Teaching science content in nursing programs in Australia: a cross-sectional survey of academics. - Birks, Melanie; Ralph, Nicholas; Cant, Robyn; Hillman, Elspeth; Ylona Chun Tie (BMC Nursing, 2015)
Background: Professional nursing practice is informed by biological, social and behavioural sciences. In undergraduate pre-registration nursing programs, biological sciences typically include anatomy, physiology, microbiology, chemistry, physics and pharmacology. The current gap in the literature results in a lack of information about the content and depth of biological sciences being taught in nursing curricula. The aim of this study was to establish what priority is given to the teaching of science topics in these programs in order to inform an understanding of the relative importance placed on this subject area in contemporary nursing education. Method: This study employed a cross-sectional survey method. This paper reports on the first phase of a larger project examining science content in nursing programs. An existing questionnaire was modified and delivered online for completion by academics who teach science to nurses in these programs. This paper reports on the relative priority given by respondents to the teaching of 177 topics contained in the questionnaire. Results: Of the relatively small population of academics who teach science to nursing students, thirty (n = 30) completed the survey. Findings indicate strong support for the teaching of science in these programs, with particular priority given to the basic concepts of bioscience and gross system anatomy. Of concern, most science subject areas outside of these domains were ranked as being of moderate or low priority. Conclusion: While the small sample size limited the conclusions able to be drawn from this study, the findings supported previous studies that indicated inadequacies in the teaching of science content in nursing curricula. Nevertheless, these findings have raised questions about the current philosophy that underpins nursing education in Australia and whether existing practices are clearly focused on preparing students for the demands of contemporary nursing practice. Academics responsible for the design and implementation of nursing curricula are encouraged to review the content of current programs in light of the findings of this research.